Surgical protocol violations in children with renal tumors provides an opportunity to improve pediatric cancer care: a report from the Children's Oncology Group. Issue 11 (27th May 2016) - Ehrlich, Peter F.; Hamilton, Thomas E.; Gow, Kenneth; Barnhart, Douglas; Ferrer, Fernando; Kandel, Jessica; Glick, Richard; Dasgupta, Roshni; Naranjo, Arlene; He, Ying; Perlman, Elizabeth J.; Kalapurakal, John A.; et al.
Abstract: Background: The purpose of this study was to evaluate the frequency and characteristics of surgical protocol violations (SPVs) among children undergoing surgery for renal tumors who were enrolled on the Children's Oncology Group (COG) renal tumor biology and classification study AREN03B2. Methods: AREN03B2 was opened in February 2006, and as on March 31, 2013, there were 3, 664 eligible patients. The surgical review forms for 3, 536 patients with unilateral disease were centrally reviewed for SPVs. The frequency, type, number of violations, institutional prevalence, and quartiles for SPVs were assessed. Results: Of the 3, 536 patients, there were a total of 505 with at least one SPV (564 total SPVs reported), for an overall incidence of 14.28%. The types of SPVs included a lack of lymph node sampling in 365 (64.7%), avoidable spill in 61 (10.8%), biopsy immediately before nephrectomy in 89 (15.8%), an incorrect abdominal incision in 32 (5.7%), and unnecessary resection of organs in 17 (3.0%). The SPVs occurred in 163 of 215 participating institutions (75.8%). For centers with at least one SPV, the mean number of SPVs reported was 3.10 ± 2.39 (mean ± standard deviation). The incidence of protocol violation per institution ranged from 0 to 67%. Centers with an average of ≤1 case/year had an incidence of SPVs of 12.2 ± 3.8%, those with an average of >1 to <4 cases/year had an incidence of SPVs of 16.4 ± 3.6%, and those with an average of ≥4 cases/year had an incidence of SPVs of 12.6 ± 5.5% ( P > 0.05). Conclusions: SPVs that potentially result in additional exposure to chemotherapy and radiation therapy are not uncommon in children undergoing resection of renal malignancies.